Model Pembelajaran Generatif Terhadap Hasil Belajar Kimia Pada Materi Ikatan Kimia - TIURLINA SIREGAR; MARIANA NENSI (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2020)
Using conventional learning methods for students who get bored quickly and are not interested in chemistry lessons. These challenges require problem solving through the learning activities provided. Learning can be done with learning models that are appropriate to the characteristics of chemicals. One learning model that provides opportunities for participants to develop their knowledge through direct experience and indirect experience is the generative learning model. The sample in this study was class X as many as 34 people. The method in this research is the design of one group pretest posttest. The purpose of this study is to study and improve the learning outcomes of chemicals in chemical bonds (n-Gain) using generative learning models in automotive class X students of SMK Negeri 3 Jayapura. Learning that involves and enhances chemistry learning outcomes in chemical bonding materials (n-Gain) using generative learning models in automotive class X students of SMK Negeri 3 Jayapura with an average n-Gain value of RPP 1 of 0.62, RPP 2 of 0 68 and RPP 3 are 0.79. The average n-Gain value of RPP 1, RPP 2 and RPP 3 is 0.71 (high category).